Strengthening Community Capacity in Disaster Mitigation Through KBLK in Bukittinggi City - Muhamad Aldi Juanda; Welhendri Azwar; Muhamad Jamil (UIN Siber Syekh Nurjati Cirebon, 2024)
This study focuses on strengthening community capacity in disaster mitigation through KBLK in Bukittinggi City. BPBD Bukittinggi City formed KBLK to focus on disaster mitigation activities and their role in disaster management. The main objective of this disaster mitigation activity is to increase community capacity in dealing with disaster risks, both through understanding, preparedness, and preventive actions. This study aims to explore the types of activities carried out by KBLK related to strengthening community capacity in disaster mitigation and the role of KBLK in these efforts. The research method used is qualitative with a descriptive approach. Research informants include the head of KBLK, village heads, disaster volunteers, and Kalaksa BPBD Bukittinggi City. Data were collected through observation, interviews, and documentation. The results of the study indicate that five KBLK organizations in Bukittinggi City have implemented various disaster mitigation programs that focus on strengthening community capacity, including risk assessment, response planning and contingency plans, the establishment of PRB forums, increasing community capacity, and integrating disaster risk reduction into village development plans. This disaster mitigation program is felt positively by the community, who become more aware, alert, and understand the importance of disaster mitigation. The community also understands more about the conditions of their area, and is able to analyze and carry out evacuation independently in the event of a disaster.